PENDIDIKAN POLITIK TENTANG KEKERASAN SEKSUAL DI LINGKUNGAN SEKOLAH KOTA BANDUNG - Mustofa, Mustabsyirotul Ummah; Paskarina, Caroline; Rahmatunnisa, Mudiyati; Herdiansah, Ari Ganjar (Universitas Padjadjaran, 2025)
Sexual violence in the school environment is a phenomenon that needs serious attention. As one of the educational sins according to the Ministry of Education and Culture, sexual violence in the school environment needs to be understood and addressed by various parties, one of which is through socialisation and political education on sexual violence. This political education activity was organised as an effort to reduce the number of cases of sexual violence in the school environment. This political education on sexual violence uses a board game as a learning medium that facilitates school students' understanding of the issues presented. The activity involved the participation of various parties, namely SMAN 25 Bandung City, SMAN 12 Bandung City, Daarut Tauhid High School, the West Java OSIS Forum (FOJB), and Mekarjaya Village PKK Cadre, Bandung City. Political education activities include discussions related to what sexual violence is, the kinds of sexual violence that we are aware of or rarely realise, power relations (body politics), and how to handle sexual violence. Activities are packaged in the form of board games, survey participation, and theatre. This activity provides an overview and fosters public awareness of the importance of the issue of sexual violence. With this awareness, it is hoped that students and the community can prevent or respond effectively if sexual violence occurs around them. Kekerasan seksual di lingkungan sekolah merupakan fenomena yang perlu mendapat perhatian serius. Sebagai salah satu dosa pendidikan menurut Kementrian Pendidikan dan Kebudayaan, kekerasan seksual di lingkungan sekolah perlu dipahami dan ditangani oleh berbagai pihak, salah satunya melalui sosialisasi dan pendidikan politik mengenai kekerasan seksual. Kegiatan edukasi politik ini diselenggarakan sebagai satu upaya mengurangi angka kekerasan seksual di lingkungan sekolah. Edukasi politik tentang kekerasan seksual ini menggunakan board game sebagai medium pembelajaran yang memudahkan pemahaman siswa-siswi sekolah terhadap isu yang disampaikan. Kegiatan melibatkan partisipasi dari berbagai pihak, yakni SMAN 25 Kota Bandung, SMAN 12 Kota Bandung, SMA Daarut Tauhid, Forum Osis Jawa Barat (FOJB), serta Kader PKK Kelurahan Mekarjaya Kota Bandung. Kegiatan pendidikan politik meliputi pembahasan terkait, apa itu kekerasan seksual, macam-macam kekerasan seksual baik yang disadari ataupun jarang kita sadari, relasi kuasa (politik tubuh), dan cara penanganan kekerasan seksual. Kegiatan dikemas dalam bentuk board game, pengisian survei serta pematerian. Kegiatan ini memberikan gambaran dan menumbuhkan kesadaran masyarakat akan pentingnya isu kekerasan seksual. Dengan kesadaran tersebut diharapkan siswa dan masyarakat dapat mencegah ataupun menanggulangi jikalau terjadi kekerasan seksual di sekitar mereka.